Two Projects - Michel Kagan (Oz, 1998)
The seat of the HLM offices at Alençon in lower Normandy is located in an uncrowded quarter made up of small two-story homes. The integrating principle consisted of building along the street in a continuous manner while freeing up a space in the center of the site for a garden structured on a play of stone walls.